Pengaruh Kedisiplinan Dan Insentif Terhadap Kinerja Pegawai Pada Badan Pengelolaan Keuangan Pendapatan Dan Aset Daerah Kota Sibolga - Nia Hasanah Hutabarat (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of Discipline and Incentives on Employee Performance at the Regional Financial, Revenue, and Asset Management Agency of Sibolga City. The population in this study consisted of 60 employees, and since the population was fewer than 100 individuals, all members of the population were used as the sample (census sampling). This research employed a quantitative approach using multiple linear regression analysis with SPSS version 23 at a 5% significance level (α = 0.05). The results indicate that partially, Discipline has a positive and significant effect on Employee Performance with a t-value of 10.489 and a significance value of 0.000 < 0.05, while Incentives also have a positive and significant effect on Employee Performance with a t-value of 2.232 and a significance value of 0.030 < 0.05. Simultaneously, Discipline and Incentives significantly influence Employee Performance, as indicated by an F-value of 75.792 and a significance value of 0.000 < 0.05. The regression equation obtained is Y = 13.184 + 0.616X1 + 0.139X2. The coefficient of determination (Adjusted R Square) of 0.727 shows that 72.7% of the variation in Employee Performance can be explained by Discipline and Incentives, while the remaining 27.3% is influenced by other variables not examined in this study. Therefore, improving discipline and providing appropriate incentives can enhance employee performance optimally.